Phenolic content and antioxidant activity of the Croatian red clover germplasm collection - Horvat, Daniela; Tucak, Marijana; Viljevac Vuletić, Marija; Čupić, Tihomir; Krizmanić, Goran; Kovačević Babić, Marija (2020)
The leaf samples of two varieties, twenty breeding populations, and seven local populations of the Croatian red clover were collected in the full flowering stage, with an aim to evaluate their phenolic content and antioxidant activity by using the spectrophotometric methods. A significant variation among the varieties/populations in the content of total phenolics and flavonoids was determined. The results demonstrated that the red clover is a rich source of phenolics and flavonoids, ranging from 38.67 to 59.96 mg GAE/g of DM and 21.19 to 51.48 mg CE/g of DM, respectively. The high levels in both phenolics and flavonoids were found in breeding populations/variety CD-8, Rc-11/7, Rc-11/8, Rc-11/15 and OS Osiris. The leaf extracts manifested a strong antioxidant activity towards diphenyl-1-picrylhydrazyl (DPPH), with a variation from 31.50 to 63.14%. A significant correlation was found between the antioxidant activity of the extracts and their total phenolic and flavonoid content (r = 0.737 and 0.839, respectively). Considering the obtained results, the crude extracts of red clover manifested a significant antioxidant potential and can be used as a natural source of biologically active components in the human and animal nutrition.
Listovi crvene djeteline uzorkovani su u fazi pune cvatnje s dvije sorte, dvadeset oplemenjivačkih populacija i sedam lokalnih populacija crvene djeteline u Hrvatskoj s ciljem određivanja ukupnih fenola i flavonoida i njihove antioksidacijske aktivnosti spektrofotometrijskim metodama. Pronađena je statistički značajna varijabilnost među sortama/populacijama u ukupnome sadržaju fenola i flavonoida. Rezultati su pokazali da je crvena djetelina bogat izvor fenola s rasponom koncentracija od 38,67 do 59,96 mg GAE/g u ST te flavonoida od 21,19 do 51,48 mg CE/g u ST. Visoka koncentracija fenola i flavonoida izmjerena je u oplemenjivačkim populacijama/sortama CD-8, Rc-11/7, Rc-11/8, Rc-11/15 i OS Osiris. Biljni ekstrakt dobiven iz lista crvene djeteline imao je snažnu antioksidacijsku aktivnost prema difenil-1-pikrilhidrazilu (DPPH) s varijabilnošću od 31,50 do 63,14%, koja statistički značajno korelira sa sadržajem ukupnih fenola (r = 0,737) i flavonoida (r = 0,839). Dobiveni rezultati pokazuju da sirovi ekstrakti crvene djeteline imaju značajan antioksidacijski potencijal, pa se stoga mogu koristiti kao prirodan izvor biološki aktivnih tvari u prehrani ljudi i ishrani životinja.
Bibliografija: 32 jed.
Summary ; Sažetak.
Keywords: Crvena djetelina -- Trifolium pratense -- Fenoli -- Flavonoidi -- Antioksidativna aktivnost